(untitled) (Research, Society and Development, 2022)
The issue of development of the educational process is a complex issue, especially when it involves Attention Deficit Hyperactivity Disorder (ADHD). The main theoretical currents emphasize the symptomatic triad that is inattention, hyperactivity and impulsivity. This symptomatic context and its consequences in the school environment have consequences for the schooling of this population. The present study is justified by the need for greater understanding of the consequences of ADHD for the schooling process and aims to highlight some consequences, bringing a brief historical-cultural concept of the Disorder, presenting symptoms and the learning disorder. For this purpose, a descriptive bibliographic research was used. The search was carried out in a virtual environment in which scientific articles are found in databases, publications and books in pdf format, with the descriptors learning, schooling and ADHD. A textual analysis was carried out on the material found, seeking concepts, relationships and clarifications on results and consequences. The results and discussions are presented in three titles, and the conclusions are presented in the final considerations.